Zirconium hydroxide powder material as well as preparation method and defluorination application thereof

By preparing zirconium hydroxide powder materials with porous structure and high specific surface area, the existing fluorine removal agents are solved and the adsorption activity is insufficient, and the effect of efficient fluorine removal and material regeneration is achieved.

CN119591151APending Publication Date: 2025-03-11HUNAN BRUNP RECYCLING TECH CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411768168.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing zirconium hydroxide-based fluorine-depleting agents require a large amount in the fluorine removal process, and due to the limitations of the particle surface, the adsorption activity is insufficient, making it difficult to efficiently remove fluorine ions in the solution.

Method used

A zirconium hydroxide powder material with a porous structure is adopted, with its main crystal form ZrO(OH)2, which has a high specific surface area and adsorption activity. By mixing with ammonia water and microwave heating treatment, a material with high fluorine removal effect is generated.

Benefits of technology

The adsorption activity and fluorine removal efficiency of zirconium hydroxide powder material are improved, the amount of fluorine removal agent is reduced, and the material still maintains good fluorine removal performance after regeneration treatment, reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591151A_ABST
    Figure CN119591151A_ABST
Patent Text Reader

Abstract

The invention discloses a zirconium hydroxide powder material and a preparation method and defluorination application thereof. The zirconium hydroxide powder material comprises ZrO (OH) 2, the specific surface area is larger than 55.7 m < 2 > / g, and the zirconium hydroxide powder material has high adsorption activity, has a good defluorination effect when applied to defluorination of an aqueous solution and plays a role in reducing the dosage of a defluorination agent. The zirconium hydroxide powder material is good in regeneration effect after defluorination, the regeneration process is simple, and the consumed time is short. The zirconium hydroxide powder is obtained by mixing commercially available zirconium hydroxide with ammonia water, standing and then carrying out heat treatment, and the method is simple, controllable and suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of wastewater treatment, and in particular to a zirconium hydroxide powder material, a preparation method thereof and a fluorine removal application thereof. Background Art

[0002] With the vigorous development of modern industrial technology, especially the large-scale construction of factories in the electronics, metallurgy, steelmaking, aluminum electrolysis, chemical industry, pesticide and other industries, the amount of fluorine-containing liquid increases significantly every year. If it is not handled properly, it will cause great harm to the environment, soil, and human health. It will also cause corrosion to production equipment during production, deteriorate the production environment of the enterprise, and be brought into the product, causing the product to be unqualified. Therefore, it is necessary to defluorinate the fluorine-containing solution to eliminate fluorine pollution.

[0003] The more mature defluorination methods in industrial production currently include chemical precipitation, flocculation precipitation, adsorption exchange, reverse osmosis, electrodialysis, and electrocoagulation. In recent years, zirconium hydroxide defluoridation agents have received attention and their application has been promoted. Zirconium hydroxide defluoridation agents are insoluble in aqueous solutions, have a large adsorption capacity, and strong adsorption ability. They can adsorb fluoride ions in water to their surface. The active hydroxyl sites distributed on the surface of zirconium hydroxide can exchange ions with the adsorbed fluoride ions to generate zirconium fluoride substances with more stable properties, which play a role in selectively and efficiently removing fluoride ions in the solution. The zirconium hydroxide after defluorination can be reused after regeneration treatment, which plays a great role in reducing production costs.

[0004] In the actual defluorination application process, due to the limitation of the surface of zirconium hydroxide particles, 1 mol of Zr(OH)4 is difficult to replace 4 mol of F - In order to achieve the effect of generating ZrF4, the input amount needs to be increased to achieve the purpose of fluorine removal. For example, in patent CN117105248A, the amount of zirconium hydroxide used for defluorination is 20-100 times the total mass of fluorine in the solution. In the article "Experimental Study on the Removal of Fluoride Ions by Nickel Sulfate System" (Chemistry and Chemical Engineering, 2020: 114-116) published by Chen Jixian, the amount of zirconium hydroxide input is more than 24 times the total mass of fluorine in the liquid after the reaction, and the zirconium-fluorine molar ratio exceeds 1.26 times. Therefore, improving the adsorption activity of zirconium hydroxide and improving its fluorine removal efficiency are of great significance to reducing the amount of zirconium hydroxide used.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The present invention proposes a zirconium hydroxide powder material and a preparation method thereof, aiming to provide a zirconium hydroxide powder material with a porous structure, which has a high specific surface area and adsorption activity, has a good defluorination effect when applied to defluorination of aqueous solution, and plays a role in reducing the amount of defluorination agent used.

[0007] The present invention is achieved in that: In a first aspect, the present invention provides a zirconium hydroxide powder material, the zirconium hydroxide powder material comprises ZrO(OH)2, and has a specific surface area greater than 55.7 m 2 / g.

[0008] Compared with Zr(OH)4, the molecular structure of ZrO(OH)2 has two fewer -OH bonds, which is conducive to combining with the electron orbital of fluoride ions. At the same time, ZrF x (OH) (4-x) It will continuously disintegrate from the surface of ZrO(OH)2 powder particles, exposing unreacted ZrO(OH)2, thereby producing a highly efficient defluorination effect and achieving the purpose of reducing the amount of defluorination agent used; in addition, the disintegrated powder is dispersed in the solution in the form of extremely fine particles, and it has a large specific surface area and can continue to react with fluorine in the solution, achieving a deep defluorination effect.

[0009] In addition, the zirconium hydroxide powder material has a larger specific surface area, thus exposing more adsorption active sites and increasing the contact area with the fluorine-containing solution, thereby further improving the defluorination efficiency and reducing the amount of defluorination agent used.

[0010] In some embodiments of the present invention, the median particle size Dv50 of the zirconium hydroxide powder material is 3.5-22.1 μm.

[0011] In some embodiments of the present invention, the specific surface area of ​​the zirconium hydroxide powder material is 55.7 to 176.6 m 2 / g.

[0012] In some embodiments of the present invention, the average pore size of the zirconium hydroxide powder material is 2.4-34.7 nm.

[0013] In some embodiments of the present invention, the total pore volume of the zirconium hydroxide powder material is 0.13-0.57 cm 3 / g.

[0014] In some embodiments of the present invention, the content of ZrO(OH)2 in the zirconium hydroxide powder material is greater than that of Zr(OH)4.

[0015] In a second aspect, the present invention provides a method for preparing a zirconium hydroxide powder material according to any of the above embodiments, comprising the following steps: The commercially available zirconium hydroxide is mixed with ammonia water, left to stand, and then subjected to microwave heating treatment, and then dried to obtain a zirconium hydroxide powder material; the commercially available zirconium hydroxide is an amorphous composition, including Zr4(OH)8(OH)8·nH2O, Zr4O2(OH)4(OH)8·nH2O and Zr4O4(OH)8·nH2O.

[0016] The ammonia molecules in the ammonia water carry free electron pairs, which can adapt to and fill the empty electron orbits of the zirconium atoms, thereby promoting the combination of the two to form a compound. On the one hand, the compound is easy to decompose under heating conditions to form ZrO(OH)2; on the other hand, the compound can release ammonia gas under heating conditions and escape from the solid to form micropores, which is beneficial to increase the specific surface area of ​​ZrO(OH)2.

[0017] In some embodiments of the present invention, the mass ratio of commercially available zirconium hydroxide to ammonia water is 1:10% to 30%.

[0018] In some embodiments of the present invention, the mass percentage of ammonia in the ammonia water is 5% to 15%.

[0019] In some embodiments of the invention, the mixing is performed in a ribbon mixer.

[0020] In some embodiments of the present invention, the standing time is 30 to 90 min.

[0021] In some embodiments of the present invention, the temperature of the microwave heating treatment is 150-250° C., and the time of the microwave heating treatment is 30-70 min.

[0022] In a third aspect, the present invention provides the zirconium hydroxide powder material of any of the above embodiments, or the use of the zirconium hydroxide powder material prepared by the preparation method of any of the above embodiments in the field of fluorine removal, comprising: putting the zirconium hydroxide powder material into a fluorine-containing solution, stirring and separating the solid and liquid to obtain a defluorinated liquid and a defluorinated slag.

[0023] In some embodiments of the present invention, the mass of the zirconium hydroxide powder material is 4.5 to 9 times the mass of the fluorine element in the fluorine-containing solution.

[0024] In some embodiments of the present invention, the stirring comprises: adding sulfuric acid to control the pH of the solution to 4-5, controlling the temperature to 60-80° C., and stirring for 60-120 min.

[0025] In some embodiments of the present invention, the defluorination residue is regenerated into a zirconium hydroxide powder material by the following method: (1) the defluorination residue is sequentially washed with water, leached with alkali, and washed with water to obtain regenerated zirconium hydroxide; (2) the regenerated zirconium hydroxide is mixed with ammonia water, allowed to stand, and then heat-treated, and dried to obtain a zirconium hydroxide powder material.

[0026] In some embodiments of the present invention, the alkaline leaching refers to placing the defluorinated residue after water washing in a sodium hydroxide solution and stirring.

[0027] In some embodiments of the present invention, the mass ratio of the regenerated zirconium hydroxide to ammonia water is 1:20%~40%.

[0028] In some embodiments of the present invention, the mass percentage of ammonia in the ammonia water is 10% to 20%.

[0029] In some embodiments of the present invention, the standing time is 90 to 150 min.

[0030] In some embodiments of the present invention, the heat treatment is performed in a microwave heating system, the heat treatment temperature is 200-300° C., and the heat treatment time is 20-60 min.

[0031] The present invention has the following beneficial effects: (1) The main crystal form of the zirconium hydroxide powder material provided by the present invention is ZrO(OH)2, and it has a high specific surface area, so it has a high adsorption activity and has a good defluorination effect when applied to defluorination of aqueous solution, thereby reducing the amount of defluorination agent used.

[0032] (2) The zirconium hydroxide powder material provided by the present invention has good regeneration effect after defluorination, and the regeneration process is simple and time-saving, which is conducive to reducing costs.

[0033] (3) The present invention provides a method for preparing the zirconium hydroxide powder material, wherein commercially available zirconium hydroxide is treated with ammonia water and further heated to obtain zirconium hydroxide powder with a high ZrO(OH)2 content and a porous structure. The method is simple and controllable and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0035] Figure 1 XRD pattern of commercially available zirconium hydroxide used in the present invention; Figure 2 This is the XRD pattern of the zirconium hydroxide powder material prepared in Example 1 of the present invention; Figure 3 This is the XRD pattern of the zirconium hydroxide prepared in Comparative Example 1 of the present invention; Figure 4 This is the XRD diagram of the zirconium hydroxide powder material prepared in Comparative Example 3 of the present invention; Figure 5 This is the XRD diagram of the defluorination slag after the first defluorination in Example 11 of the present invention; Figure 6 This is the XRD diagram of the zirconium hydroxide powder material regenerated after the first defluorination in Example 11 of the present invention. DETAILED DESCRIPTION

[0036] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0037] In the description of the embodiments of the present application, technical terms such as "first" and "second" are only used to distinguish different objects and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features.

[0038] Reference to "embodiment" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiment may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments.

[0039] In the embodiment of the present application, the term "or / and" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A or / and B can represent three situations: A exists alone, A and B exist at the same time, and B exists alone.

[0040] In addition, the character “ / ” in this article generally indicates that the previous and next associated objects are in an “or” relationship.

[0041] In the embodiments of the present application, the meaning of "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multi-layer" refers to more than two layers (including two layers), unless otherwise clearly specified and limited.

[0042] In the embodiments of the present application, "at least one" means one or more than one.

[0043] In the embodiments of the present application, the orientations or positional relationships indicated by the technical terms "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", etc. are based on the orientations or positional relationships shown in the drawings, and are only for the convenience of describing the embodiments of the present application and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed in a specific orientation, etc., and cannot be understood as limiting the embodiments of the present application. Those skilled in the art can understand the specific meanings of the above terms in the embodiments of the present application according to specific circumstances.

[0044] In a first aspect, the present invention provides a zirconium hydroxide powder material, the zirconium hydroxide powder material comprises ZrO(OH)2, and has a specific surface area greater than 55.7 m 2 / g.

[0045] The main crystal form of the zirconium hydroxide powder material provided by the present invention is ZrO(OH)2. Compared with the commercially available zirconium hydroxide (including a combination of various crystal forms such as Zr4(OH)8(OH)8·nH2O, Zr4O2(OH)4(OH)8·nH2O and Zr4O4(OH)8·nH2O, XRD shows that it is an amorphous substance), the zirconium atom in the ZrO(OH)2 molecule is connected to an oxygen atom, replacing the position of two -OH bonds, so that the steric hindrance of the zirconium atom is reduced, which is conducive to combining with the fluoride ion electron orbit, and thus has a higher adsorption activity. Furthermore, ZrF x (OH) (4-x) It can continuously disintegrate from the surface of ZrO(OH)2 powder particles, exposing unreacted ZrO(OH)2, thereby improving the utilization rate of active substances in zirconium hydroxide powder and achieving the purpose of reducing the amount of defluorination agent; furthermore, the disintegrated ZrF x (OH) (4-x) The powder is dispersed in the solution in the form of extremely fine particles. Due to its large specific surface area, it can continue to react with fluorine in the solution, achieving the effect of deep defluorination, further improving the utilization rate of active substances and achieving the purpose of reducing the amount of defluorination agent used.

[0046] In addition, the zirconium hydroxide powder material provided by the present invention has a larger specific surface area, thereby exposing more adsorption active sites and increasing the contact area with the fluorine-containing solution, thereby further improving the defluorination efficiency and reducing the amount of defluorination agent used.

[0047] In some embodiments of the present invention, the specific surface area of ​​the zirconium hydroxide powder material is 55.7~176.6m 2 / g.

[0048] In some embodiments of the present invention, the median particle size Dv50 of the zirconium hydroxide powder material is 3.5~22.1 μm; for example, it can be 3.5 μm, 5.5 μm, 7.5 μm, 9.5 μm, 11.5 μm, 13.5 μm, 16.1 μm, 18.4 μm, 20.2 μm, 22.1 μm, etc. or any value between the above values. The particle size of the zirconium hydroxide powder material will affect its specific surface area, thereby affecting the defluorination effect. If the particle size is too large, the specific surface area will be smaller; if the particle size is too small, although it is beneficial to improve the defluorination efficiency, it is not conducive to solid-liquid separation after defluorination.

[0049] In some embodiments of the present invention, the average pore size of the zirconium hydroxide powder material is 2.4~34.7 nm, for example, it can be 2.5 nm, 5.8 nm, 8.8 nm, 15.9 nm, 22.6 nm, 27.5 nm, 34.5 nm, etc. or any value between the above values; the average pore size can reflect the defluorination activity of the zirconium hydroxide powder material. The smaller the pore size, the fewer the types of ions that can freely enter and exit the channel, which is more conducive to fluoride ions with a small ion radius entering the reaction channel, thereby improving the defluorination selectivity.

[0050] In some embodiments of the present invention, the total pore volume of the zirconium hydroxide powder material is 0.13-0.57 cm 3 / g, for example, it can be 0.14 cm 3 / g, 0.20cm 3 / g, 0.26cm 3 / g, 0.32cm 3 / g, 0.38cm 3 / g, 0.44cm 3 / g, 0.50cm 3 / g, 0.56cm 3 / g or any value between the above values; the total pore volume can reflect the porosity of the zirconium hydroxide powder material. The larger the total pore volume, the larger the porosity of the zirconium hydroxide powder material, indicating that the larger the specific surface area, the more conducive to fluorine removal.

[0051] In some embodiments of the present invention, the content of ZrO(OH)2 in the zirconium hydroxide powder material is greater than that of Zr(OH)4; specifically, the mass proportion of ZrO(OH)2 in the zirconium hydroxide powder material is above 50%, and may be 50%-60%, 60%-70%, 70%-80%, 80%-90%, 90%-100%, 60%-100%, 70%-100%, 80%-100%, etc. The mass proportion of ZrO(OH)2 in the zirconium hydroxide powder material affects its defluorination effect, thereby affecting its feed amount during defluorination.

[0052] In a second aspect, the present invention provides a method for preparing the zirconium hydroxide powder material of any of the above embodiments, comprising the following steps: The commercially available zirconium hydroxide is mixed with ammonia water, left to stand, and then subjected to microwave heating treatment, and then dried to obtain a zirconium hydroxide powder material; the commercially available zirconium hydroxide is an amorphous composition, including Zr4(OH)8(OH)8·nH2O, Zr4O2(OH)4(OH)8·nH2O and Zr4O4(OH)8·nH2O.

[0053] The present invention uses ammonia water to perform alkali treatment on commercially available zirconium hydroxide. The N atoms in the ammonia molecules carry free electron pairs, which can fill the empty electron orbits of the zirconium atoms to form a combination; the combination is easily decomposed under heating conditions to generate ZrO(OH)2 and ammonia. When the ammonia escapes from the solid, fine pores are formed, thereby increasing the specific surface area of ​​ZrO(OH)2.

[0054] The present invention heats the material through a microwave heating system, and utilizes high-frequency electromagnetic wave heating to ensure that the zirconium hydroxide treated with ammonia water is heated evenly during the thermal decomposition process, thereby avoiding excessive decomposition caused by excessive local temperature to generate ZrO2 with poor defluorination activity.

[0055] In some embodiments of the present invention, the mass ratio of commercially available zirconium hydroxide to ammonia water is 1:10%~30%; the amount of alkaline solution (ammonia water) used in the alkaline treatment of commercially available zirconium hydroxide in the present invention is lower than that of commercially available zirconium hydroxide, which is beneficial to reducing costs on the one hand; on the other hand, it can prevent the zirconium hydroxide particles from being excessively wetted and agglomerated. The zirconium hydroxide agglomerates will further solidify into high-hardness agglomerates during heat treatment, making them difficult to disperse, resulting in a significant reduction in their specific surface area, which is not conducive to fluorine removal.

[0056] In some embodiments of the present invention, the mass percentage of ammonia in the ammonia water is 5% to 15%.

[0057] In some embodiments of the present invention, the mixing is performed in a ribbon mixer.

[0058] The ribbon mixer, with its unique mixing structure and efficient mixing capacity, can ensure that the materials are fully and evenly mixed during the mixing process. Specifically, the equipment lifts the materials from the bottom to the top through the rotation and scraping of the ribbon, and then throws them into the mixing chamber, achieving all-round mixing in three-dimensional space, which can effectively avoid agglomeration and stratification of materials.

[0059] In some embodiments of the present invention, a ribbon mixer is used to mix commercially available zirconium hydroxide and ammonia water at a mass ratio of 1:10% to 30%. The ribbon mixer can ensure that each zirconium hydroxide particle is in full contact with the ammonia water to form an ideal wet state that is neither too dry nor too wet, thereby improving the reaction efficiency while avoiding particle agglomeration.

[0060] In some embodiments of the present invention, the standing time is 30 to 90 minutes.

[0061] After being evenly mixed, the wet zirconium hydroxide is allowed to stand for a period of time, which is beneficial to further stabilize and homogenize its internal structure. Through the standing treatment, the zirconium hydroxide particles can absorb ammonia water more fully, thereby improving the utilization rate of ammonia water.

[0062] In some embodiments of the present invention, the temperature of the microwave heating treatment is 150-250° C., and the time of the microwave heating treatment is 30-70 min.

[0063] In a third aspect, the present invention provides the zirconium hydroxide powder material of any of the above embodiments, or the application of the zirconium hydroxide powder material prepared by the preparation method of any of the above embodiments in the field of fluorine removal, comprising: putting the zirconium hydroxide powder material into a fluorine-containing solution, stirring and separating the solid and liquid to obtain a defluorinated liquid and a defluorinated slag.

[0064] In some embodiments of the present invention, the mass of the zirconium hydroxide powder material is 4.5 to 9 times the mass of the fluorine element in the fluorine-containing solution.

[0065] In some embodiments of the present invention, the stirring comprises: adding sulfuric acid to control the pH of the solution to 4-5, controlling the temperature to 60-80° C., and stirring for 60-120 min.

[0066] In some embodiments of the present invention, the defluorination residue is regenerated into a zirconium hydroxide powder material by the following method: (1) the defluorination residue is sequentially washed with water, leached with alkali, and washed with water to obtain regenerated zirconium hydroxide; (2) the regenerated zirconium hydroxide is mixed with ammonia water, allowed to stand, and then heat-treated, and dried to obtain the regenerated zirconium hydroxide powder material.

[0067] In some embodiments of the present invention, the alkaline leaching refers to placing the defluorination residue after water washing in a sodium hydroxide solution and stirring; the concentration of the sodium hydroxide solution can be 1~3mol / L, for example, 1mol / L, 2mol / L, 3mol / L, etc. or any value between the above values; the stirring time can be 0.5~1.5h, for example, 0.5h, 1h, 1.5h, etc. or any value between the above values.

[0068] In some embodiments of the present invention, the mass ratio of the regenerated zirconium hydroxide to ammonia water is 1:20%~40%.

[0069] In some embodiments of the present invention, the mass percentage of ammonia in the ammonia water is 10% to 20%.

[0070] In some embodiments of the present invention, the standing time is 90 to 150 minutes.

[0071] In some embodiments of the present invention, the heat treatment is performed in a microwave heating system, the heat treatment temperature is 200-300° C., and the heat treatment time is 20-60 min.

[0072] The process of regenerating regenerated zirconium hydroxide to prepare regenerated zirconium hydroxide powder material is similar to that of using commercially available zirconium hydroxide to prepare zirconium hydroxide powder material, but the amount of ammonia used is relatively large, and the heat treatment temperature is relatively high and the standing time is relatively long. The reason is that the structure of the zirconium hydroxide powder material changes during the defluorination and water washing / alkaline leaching processes, and it absorbs a lot of water during these two processes. It is necessary to increase the amount of ammonia water used and extend the standing time so that the ammonia water can fully complete the reaction in the zirconium hydroxide; during the heat treatment process, it is necessary to increase the heat treatment temperature or extend the heat treatment time to ensure that the structure of the zirconium hydroxide is restored to its original state.

[0073] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0074] Example 1 A method for preparing a zirconium hydroxide powder material comprises the following steps: Commercially available zirconium hydroxide and ammonia water with an ammonia concentration of 5% were weighed in a mass ratio of 1:10%, placed in a ribbon mixer for mixing, and allowed to stand for 90 minutes after mixing evenly; then placed in a microwave heating system, heated at 150°C for 70 minutes, and then vacuum dried to constant weight to obtain a zirconium hydroxide powder material.

[0075] Example 2 A method for preparing a zirconium hydroxide powder material comprises the following steps: Commercially available zirconium hydroxide and ammonia water with an ammonia concentration of 7.5% were weighed in a mass ratio of 1:15%, placed in a ribbon mixer for mixing, and allowed to stand for 75 minutes after mixing evenly; then placed in a microwave heating system, heated at 175°C for 60 minutes, and then vacuum dried to constant weight to obtain a zirconium hydroxide powder material.

[0076] Example 3 A method for preparing a zirconium hydroxide powder material comprises the following steps: Commercially available zirconium hydroxide and ammonia water with an ammonia concentration of 10% were weighed in a mass ratio of 1:20%, placed in a ribbon mixer for mixing, and allowed to stand for 60 minutes after mixing evenly; then placed in a microwave heating system, heated at 200°C for 50 minutes, and then vacuum dried to constant weight to obtain a zirconium hydroxide powder material.

[0077] Example 4 A method for preparing a zirconium hydroxide powder material comprises the following steps: Commercially available zirconium hydroxide and ammonia water with an ammonia concentration of 12.5% ​​were weighed in a mass ratio of 1:25%, placed in a ribbon mixer for mixing, and allowed to stand for 45 minutes after mixing evenly; then placed in a microwave heating system, heated at 225°C for 40 minutes, and then vacuum dried to constant weight to obtain a zirconium hydroxide powder material.

[0078] Example 5 A method for preparing a zirconium hydroxide powder material comprises the following steps: Commercially available zirconium hydroxide and ammonia water with an ammonia concentration of 15% were weighed in a mass ratio of 1:30%, placed in a ribbon mixer for mixing, and allowed to stand for 30 minutes after mixing evenly; then placed in a microwave heating system, heated at 250°C for 30 minutes, and then vacuum dried to constant weight to obtain a zirconium hydroxide powder material.

[0079] Example 6 A method for preparing a zirconium hydroxide powder material is different from that of Example 1 in that commercially available zirconium hydroxide and ammonia water with an ammonia concentration of 5% are weighed in a mass ratio of 1:5% and placed in a ribbon mixer for mixing.

[0080] Example 7 A method for preparing a zirconium hydroxide powder material is different from that of Example 1 in that commercially available zirconium hydroxide and ammonia water with an ammonia concentration of 5% are weighed in a mass ratio of 1:40% and placed in a ribbon mixer for mixing.

[0081] Comparative Example 1 A method for preparing zirconium hydroxide, which is different from Example 1 in that 5 wt % sodium hydroxide solution is used instead of ammonia water to mix with commercially available zirconium hydroxide.

[0082] Comparative Example 2 A method for preparing zirconium hydroxide comprises the following steps: Dissolve ZrOCl2 in deionized water to obtain Zr 4+A zirconium salt solution with a concentration of 1.0 mol / L was added, and then ammonia water was slowly added until the pH value of the solution reached 11.5±0.5 for precipitation reaction. After the precipitate did not increase significantly, the mixture was refluxed at 96°C for 24 h under continuous stirring, and the precipitate was separated from the solid and liquid, and the precipitate was washed with deionized water several times to remove residual chloride ions. Finally, the washed precipitate was dried at 100°C to obtain zirconium hydroxide powder.

[0083] Comparative Example 3 A method for preparing a zirconium hydroxide powder material, which is different from Example 1 in that the heat treatment is carried out by ordinary heating, specifically comprising: Commercially available zirconium hydroxide and ammonia water with an ammonia concentration of 5% were weighed in a mass ratio of 1:10%, placed in a ribbon mixer for mixing, and allowed to stand for 90 minutes after mixing evenly; then placed in an oven, heated at 150°C for 70 minutes, and then vacuum dried to constant weight to obtain a zirconium hydroxide powder material.

[0084] Table 1 shows the physical properties of the products prepared in Examples 1 to 7 and Comparative Examples 1 to 3. The specific surface area (BET) is tested by nitrogen adsorption and desorption experiments and calculated by the BET formula. The Dv50 is tested by a laser particle size analyzer.

[0085] Table 1

[0086] Analysis of the data in Table 1 shows that the specific surface area of ​​the commercially available zirconium hydroxide is greatly increased after the present invention treats it. Comparing Example 1 with Comparative Example 1, treating the commercially available zirconium hydroxide with ammonia water as an alkaline agent can effectively increase the specific surface area of ​​the product, which is beneficial to improving its fluorine removal rate. Comparing Example 1 with Comparative Example 2, the specific surface area of ​​the ZrO(OH)2 powder material prepared using ZrOCl2 as a raw material is relatively small, and the preparation process is energy-consuming and time-consuming, and the process is difficult to control, which is not suitable for industrialization. Comparing Example 1 with Comparative Example 3, the zirconium hydroxide powder obtained by microwave heating has a higher specific surface area and smaller particle size than that by ordinary oven heating. By comparing Examples 1, 6, and 7, it can be seen that the mass ratio of commercially available zirconium hydroxide to ammonia water during the preparation process affects the specific surface area and particle size of the product; specifically, if the amount of ammonia water is too little, the dispersion of the particles is poor, resulting in serious agglomeration, and thus Dv50 increases; in addition, less ammonia gas is generated during the heat treatment process, so the lower the porosity, the smaller the specific surface area of ​​the product; if the amount of ammonia water is too much, the drying process of the product is slow, agglomeration is aggravated, and thus the particle size becomes larger and the specific surface area decreases.

[0087] Nitrogen adsorption and desorption experiments were conducted on Examples 1 to 7 and Comparative Examples 1 to 3, and the surface area, average pore size and total pore volume were calculated using the BET method. The average pore size of the zirconium hydroxide powder material prepared in Examples 1 to 7 of the present invention is 2.4 to 34.7 nm; the average pore sizes of Example 1, Comparative Example 1 and Comparative Example 2 are 3.9 nm, 48.5 nm and 37.7 nm respectively, indicating that compared with the use of sodium hydroxide, the present invention uses ammonia water to treat the commercially available zirconium hydroxide, which can obtain a porous material with a finer pore size, which is beneficial to increase the specific surface area of ​​the material; the traditional method of using ZrOCl2 as a raw material to prepare the zirconium hydroxide powder material by reflux heating is that the zirconium hydroxide structure obtained by the precipitation process is relatively loose, so the average pore size of the product is larger.

[0088] The total pore volume of the zirconium hydroxide powder material prepared in Examples 1 to 7 of the present invention is 0.13 to 0.57 cm 3 / g; the total pore volumes of Example 1, Comparative Example 1, and Comparative Example 2 are 0.25 cm 3 / g, 0.09cm 3 / g, 0.11cm 3 / g, indicating that compared with the use of sodium hydroxide, the present invention uses ammonia water to treat the commercially available zirconium hydroxide to obtain a porous material with higher porosity.

[0089] Instructions attached Figure 1 : This is the XRD spectrum of commercially available zirconium hydroxide. It can be seen from the figure that commercially available zirconium hydroxide is an amorphous material.

[0090] Instructions attached Figure 2 This is the XRD diagram of the zirconium hydroxide powder material prepared in Example 1. It can be seen from the figure that the main crystal form of the zirconium hydroxide powder material is ZrO(OH)2, and a small amount of diffraction peak of Zr(OH)4 can be observed, but its related peak intensity is much lower than the characteristic diffraction peak intensity of the main crystal form ZrO(OH)2, indicating that the main crystal form is ZrO(OH)2.

[0091] Instructions attached Figure 3 This is the XRD diagram of the zirconium hydroxide prepared in Comparative Example 1 of the present invention. It can be seen from the figure that since sodium hydroxide solution is used instead of ammonia water to treat the zirconium hydroxide, the main crystal forms of the product are Zr4(OH)8(OH)8·nH2O and Zr4O2(OH)4(OH)8·nH2O, indicating that using ammonia water as a treating agent is beneficial to the formation of highly active ZrO(OH)2.

[0092] Instructions attached Figure 4This is the XRD diagram of the zirconium hydroxide powder material prepared in Comparative Example 3. It can be seen from the figure that the conventional heat treatment method will reduce the ZrO(OH)2 content in the product and increase the ZrO2 content.

[0093] Examples 9 to 15 are respectively the defluorination applications of Examples 1 to 7, and Comparative Examples 4 to 5 are the defluorination applications of Comparative Examples 1 and 3.

[0094] Example 9 (I) Using zirconium hydroxide powder material as a defluorinating agent to defluorinate a fluorine-containing solution comprises the following steps: According to the principle that the mass of the zirconium hydroxide powder material is 4.5 times the mass of the fluorine element in the fluorine-containing solution, the zirconium hydroxide powder material prepared in Example 1 is added to 5000L of the fluorine-containing solution 1, and sulfuric acid is added while stirring to maintain the pH of the solution at 4-5. The temperature during the stirring process is controlled at 70°C. After stirring for 90 minutes, solid-liquid separation is performed to obtain defluorinated slag and a first defluorinated liquid.

[0095] The composition of the fluorine-containing solution 1 is shown in Table 2.

[0096] Table 2

[0097] (ii) Regeneration of the defluorination slag includes the following steps: (1) The defluorinated residue is washed with water, then placed in a 1.0 mol / L sodium hydroxide solution and stirred for 60 min, followed by solid-liquid separation, and the solid is washed with water until the pH of the washing solution is neutral, thereby obtaining regenerated zirconium hydroxide; (2) Weigh the regenerated zirconium hydroxide and ammonia water with an ammonia concentration of 20% in a mass ratio of 1:20%, place them in a ribbon mixer for mixing, and let them stand for 90 minutes after mixing evenly; then place them in a microwave heating system, heat them at 300°C for 20 minutes, and then vacuum dry them to constant weight to obtain the regenerated zirconium hydroxide powder material.

[0098] The regenerated zirconium hydroxide powder material is put back into the defluorinated liquid and defluorinated for the second time according to the process of (i), and regenerated according to the process of (ii). The above operation is repeated until 10 defluorinations are carried out, and the element content in the defluorinated liquid is tested, and the defluorination rate and the recovery rate of other elements are calculated; defluorination rate = percentage content of F in defluorinated liquid ÷ percentage content of F in fluorine-containing solution × 100%, recovery rate = percentage content of elements in defluorinated liquid ÷ percentage content of elements in fluorine-containing solution × 100%, the results are listed in Table 2-1.

[0099] Table 2-1

[0100] It can be seen from Table 2-1 that the treated zirconium hydroxide has a higher fluorine removal effect because it generates a highly active ZrO(OH)2 crystal form.

[0101] Example 10 (I) Using zirconium hydroxide powder material as a defluorinating agent to defluorinate a fluorine-containing solution comprises the following steps: According to the principle that the mass of the zirconium hydroxide powder material is 6 times the mass of the fluorine element in the fluorine-containing solution, the zirconium hydroxide powder material prepared in Example 2 is added to 5000L of fluorine-containing solution 2, and sulfuric acid is added while stirring to maintain the pH of the solution at 4-5. The temperature during the stirring process is controlled at 70°C. After stirring for 90 minutes, solid-liquid separation is performed to obtain defluorinated slag and a first defluorinated liquid.

[0102] The composition of the fluorine-containing solution 2 is shown in Table 3.

[0103] Table 3

[0104] (ii) Regeneration of the defluorination slag includes the following steps: (1) The defluorinated residue is washed with water, then placed in a 1.0 mol / L sodium hydroxide solution and stirred for 60 min, followed by solid-liquid separation, and the solid is washed with water until the pH of the washing solution is neutral, thereby obtaining regenerated zirconium hydroxide; (2) Weigh the regenerated zirconium hydroxide and ammonia water with an ammonia concentration of 17.5% in a mass ratio of 1:25%, place them in a ribbon mixer for mixing, and let them stand for 105 minutes after mixing evenly; then place them in a microwave heating system, heat them at 275°C for 30 minutes, and then vacuum dry them to constant weight to obtain the regenerated zirconium hydroxide powder material.

[0105] The regenerated zirconium hydroxide powder material is put back into the defluorinated liquid and defluorinated for a second time according to process (i), and regenerated according to process (ii). The above operation is repeated until defluorination is performed 10 times, and the element content in the defluorinated liquid is tested. The results are listed in Table 3-1.

[0106] Table 3-1

[0107] Embodiment 11 (I) Using zirconium hydroxide powder material as a defluorinating agent to defluorinate a fluorine-containing solution comprises the following steps: According to the mass of the zirconium hydroxide powder material being 7.5 times the mass of the fluorine element in the fluorine-containing solution, the zirconium hydroxide powder material prepared in Example 3 was added to 5000L of fluorine-containing solution 3, and sulfuric acid was added while stirring to maintain the pH of the solution at 4-5. The temperature during the stirring process was controlled at 70°C. After stirring for 90 minutes, solid-liquid separation was performed to obtain defluorinated slag and a first defluorinated liquid.

[0108] The composition of the fluorine-containing solution 3 is shown in Table 4.

[0109] Table 4

[0110] (ii) Regeneration of the defluorination slag includes the following steps: (1) washing the defluorinated residue with water, then placing it in a sodium hydroxide solution with a concentration of 1.0 mol / L and stirring it for 60 min, separating the solid from the liquid, and washing the solid with water until the pH of the washing solution is neutral, thereby obtaining regenerated zirconium hydroxide; (2) Weigh the regenerated zirconium hydroxide and ammonia water with an ammonia concentration of 15% in a mass ratio of 1:30%, place them in a ribbon mixer for mixing, and let them stand for 120 minutes after mixing evenly; then place them in a microwave heating system, heat them at 250°C for 40 minutes, and then vacuum dry them to constant weight to obtain the regenerated zirconium hydroxide powder material.

[0111] The regenerated zirconium hydroxide powder material is put back into the defluorinated liquid for secondary defluorination according to process (i), and regenerated according to process (ii). The above operation is repeated for 10 defluorinations, and the element content in the defluorinated liquid is tested. The results are listed in Table 4-1.

[0112] Table 4-1

[0113] Instructions attached Figure 5 The XRD diagram of the defluorinated slag after the first defluorination of Example 11 of the present invention; Figure 6 This is the XRD diagram of the zirconium hydroxide powder material regenerated after the first defluorination in Example 11 of the present invention. It can be seen that the zirconium hydroxide powder material is converted into an amorphous form after defluorination, and can almost be restored to the ZrO(OH)2 crystal form after regeneration, and has good regeneration performance.

[0114] Example 12 (I) Using zirconium hydroxide powder material as a defluorinating agent to defluorinate a fluorine-containing solution comprises the following steps: According to the principle that the mass of the zirconium hydroxide powder material is 8 times the mass of the fluorine element in the fluorine-containing solution, the zirconium hydroxide powder material prepared in Example 4 is added to 5000L of fluorine-containing solution 4, and sulfuric acid is added while stirring to maintain the pH of the solution at 4-5. The temperature during the stirring process is controlled at 70°C. After stirring for 90 minutes, solid-liquid separation is performed to obtain defluorinated slag and a first defluorinated liquid.

[0115] The composition of the fluorine-containing solution 4 is shown in Table 5.

[0116] Table 5

[0117] (ii) Regeneration of the defluorination slag includes the following steps: (1) The defluorinated residue is washed with water, then placed in a 1.0 mol / L sodium hydroxide solution and stirred for 60 min, followed by solid-liquid separation, and the solid is washed with water until the pH of the washing solution is neutral, thereby obtaining regenerated zirconium hydroxide; (2) Weigh the regenerated zirconium hydroxide and ammonia water with an ammonia concentration of 12.5% ​​in a mass ratio of 1:35%, place them in a ribbon mixer for mixing, and let them stand for 135 minutes after mixing evenly; then place them in a microwave heating system, heat them at 225°C for 50 minutes, and then vacuum dry them to constant weight to obtain the regenerated zirconium hydroxide powder material.

[0118] The regenerated zirconium hydroxide powder material is put back into the defluorinated liquid and defluorinated for a second time according to process (i), and regenerated according to process (ii). The above operation is repeated until defluorination is performed 10 times, and the element content in the defluorinated liquid is tested. The results are listed in Table 5-1.

[0119] Table 5-1

[0120] Embodiment 13 (I) Using zirconium hydroxide powder material as a defluorinating agent to defluorinate a fluorine-containing solution comprises the following steps: According to the principle that the mass of the zirconium hydroxide powder material is 9 times the mass of the fluorine element in the fluorine-containing solution, the zirconium hydroxide powder material prepared in Example 5 is added to 5000L of the fluorine-containing solution 5, and sulfuric acid is added while stirring to maintain the pH of the solution at 4-5. The temperature during the stirring process is controlled at 70°C. After stirring for 90 minutes, solid-liquid separation is performed to obtain defluorinated slag and a first defluorinated liquid.

[0121] The composition of the fluorine-containing solution 5 is shown in Table 6.

[0122] Table 6

[0123] (ii) Regeneration of the defluorination slag includes the following steps: (1) washing the defluorinated residue with water, then placing it in a sodium hydroxide solution with a concentration of 1.0 mol / L and stirring it for 60 min, separating the solid from the liquid, and washing the solid with water until the pH of the washing solution is neutral, thereby obtaining regenerated zirconium hydroxide; (2) Weigh the regenerated zirconium hydroxide and ammonia water with an ammonia concentration of 10% in a mass ratio of 1:40%, place them in a ribbon mixer for mixing, and let them stand for 150 minutes after mixing evenly; then place them in a microwave heating system, heat them at 200°C for 60 minutes, and then vacuum dry them to constant weight to obtain the regenerated zirconium hydroxide powder material.

[0124] The regenerated zirconium hydroxide powder material is put back into the defluorinated liquid and defluorinated for a second time according to process (i), and regenerated according to process (ii). The above operation is repeated until defluorination is performed 10 times, and the element content in the defluorinated liquid is tested. The results are listed in Table 6-1.

[0125] Table 6-1

[0126] Embodiment 14 The difference from Example 9 is that the zirconium hydroxide powder material prepared in Example 6 is used as the defluorinating agent instead of Example 1 to defluorinate the fluorine-containing solution 1.

[0127] Embodiment 15 The difference from Example 9 is that the zirconium hydroxide powder material prepared in Example 7 is used as the defluorinating agent instead of Example 1 to defluorinate the fluorine-containing solution 1.

[0128] Comparative Example 4 The difference from Example 9 is that the zirconium hydroxide prepared in Comparative Example 1 is used as the defluorinating agent instead of Example 1 to defluorinate the fluorine-containing solution 1.

[0129] Comparative Example 5 The difference from Example 9 is that the zirconium hydroxide powder material prepared in Comparative Example 3 is used as the defluorinating agent instead of Example 1 to defluorinate the fluorine-containing solution 1.

[0130] The element contents in the defluorinated liquid after 10 defluorinations obtained in Example 9, Examples 14-15, and Comparative Examples 4-5 were measured, and the defluorination rate was calculated; defluorination rate = defluorinated liquid F percentage content ÷ fluorine-containing solution F percentage content × 100%. The results are listed in Table 7.

[0131] Table 7

[0132] Combined with Table 1 and Table 7, and Appendix Figures 2~4Analysis shows that the larger the specific surface area of ​​the zirconium hydroxide powder material, the higher the fluorine removal rate; the higher the ZrO(OH)2 content in the zirconium hydroxide powder material, the higher the fluorine removal rate.

[0133] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A zirconium hydroxide powder material, characterized in that: The zirconium hydroxide powder material comprises ZrO(OH)2 and has a specific surface area greater than 55.7 m 2 / g.

2. The zirconium hydroxide powder material according to claim 1, characterized in that: The median particle size Dv50 of the zirconium hydroxide powder material is 3.5-22.1 μm; Or / and, the specific surface area of ​​the zirconium hydroxide powder material is 55.7~176.6 m 2 / g; Or / and, the average pore size of the zirconium hydroxide powder material is 2.4-34.7 nm; Or / and, the total pore volume of the zirconium hydroxide powder material is 0.13-0.57 cm 3 / g; Or / and, the content of ZrO(OH)2 in the zirconium hydroxide powder material is greater than that of Zr(OH)4.

3. A method for preparing the zirconium hydroxide powder material according to claim 1 or 2, characterized in that: The following steps are involved: The commercially available zirconium hydroxide is mixed with ammonia water, left to stand, and then subjected to microwave heating treatment, and then dried to obtain a zirconium hydroxide powder material; the commercially available zirconium hydroxide is an amorphous composition, including Zr4(OH)8(OH)8·nH2O, Zr4O2(OH)4(OH)8·nH2O and Zr4O4(OH)8·nH2O.

4. The method for preparing zirconium hydroxide powder material according to claim 3, characterized in that: The mass ratio of the commercially available zirconium hydroxide to ammonia water is 1:10% to 30%; Or / and, the mass percentage of ammonia in the ammonia water is 5% to 15%; Or / and, the mixing is carried out in a ribbon mixer.

5. The method for preparing zirconium hydroxide powder material according to claim 3, characterized in that: The standing still time is 30 to 90 minutes.

6. The method for preparing zirconium hydroxide powder material according to claim 3, characterized in that: The temperature of the microwave heating treatment is 150-250° C., and the time of the microwave heating treatment is 30-70 min.

7. A defluorination application of the zirconium hydroxide powder material according to claim 1 or 2, characterized in that: The zirconium hydroxide powder material is put into the fluorine-containing solution, and the solid and liquid are separated after stirring to obtain the defluorinated liquid and the defluorinated slag.

8. The defluorination application of the zirconium hydroxide powder material according to claim 7, characterized in that: The mass of the zirconium hydroxide powder material is 4.5 to 9 times the mass of the fluorine element in the fluorine-containing solution; Or / and, the stirring comprises: adding sulfuric acid to control the pH of the solution to 4-5, controlling the temperature to 60-80° C., and stirring for 60-120 min.

9. The defluorination application of the zirconium hydroxide powder material according to claim 8, characterized in that: The defluorination residue is regenerated into a zirconium hydroxide powder material by the following method: (1) washing the defluorination residue with water, leaching with alkali, and washing with water in sequence to obtain regenerated zirconium hydroxide; (2) mixing the regenerated zirconium hydroxide with ammonia water, allowing the mixture to stand, heat treating the mixture, and drying the mixture to obtain the regenerated zirconium hydroxide powder material.

10. The defluorination application of the zirconium hydroxide powder material according to claim 9, characterized in that: The alkaline leaching refers to placing the defluorinated residue after washing in a sodium hydroxide solution and stirring; Or / and, the mass ratio of the regenerated zirconium hydroxide to ammonia water is 1:20%~40%; Or / and, the mass percentage of ammonia in the ammonia water is 10% to 20%; Or / and, the standing time is 90 to 150 min; Or / and, the heat treatment is carried out in a microwave heating system, the heat treatment temperature is 200-300°C, and the heat treatment time is 20-60 min.

Citation Information

Patent Citations

  • Method for producing battery-grade lithium carbonate by using waste NCM ternary battery powder

    CN117105248A